A Case of McLeod Syndrome with A Novel XK Missense Mutation. Issue 3 (6th April 2018) - Komiya, Hiroyasu; Takasu, Mutsuki; Hashiguchi, Shunta; Uematsu, Eri; Fukai, Ryoko; Tanaka, Kenichi; Tada, Mikiko; Joki, Hideto; Takahashi, Tatsuya; Koyano, Shigeru; Doi, Hiroshi; Takeuchi, Hideyuki; et al.
Abstract : View Supplementary Video 1 View Supplementary Video 2